Batasio convexirostrum, a new species of catfish (Teleostei: Bagridae) from Koladyne basin, India - Darshan, A.; Anganthoibi, N.; Vishwanath, W. (Zootaxa, 2011)
Batasio convexirostrum, a new bagrid catfish, is described from the Koladyne drainage, Mizoram, India. It is distinguished from congeners by a combination of the following characters: body with a dark-brown oblique predorsal bar on a uniform light-brown background; very short dorsal to adipose distance (1.7–4.1% SL); snout length 39.2–45.5% head length; eye diameter 24.6–29.8% head length; gill rakers on the first branchial arch 4–5; pectoral spine length 14.6–17.6% standard length; adipose-fin base length 31.0–34.9% standard length; post-adipose distance 10.6–13.7% standard length; branched pectoral fin rays 9–10; and 39–40 vertebrae.